Integrated Seismotectonic Analysis of the West–Central Java Subduction System Based on Seismicity, Focal Mechanisms, and Seismic Tomography - Zahrani, Deanne Ardelia; Winusda, Sinta Caenur; Hasanah, Mia Uswatun (Universitas Islam Negeri Ar-Raniry, 2027)
Java Island lies along the convergent boundary between Indo-Australian and Eurasian plates, making it one of the most seismically active regions in Indonesia. Numerous studies have investigated seismicity, focal mechanisms, and seismic tomography beneath West and Central Java. However, these datasets are commonly interpreted separately, and integrated assessments of slab geometry and deformation variations along subduction zone remain limited. This study combines data from ISC-EHB (1964–2022), BMKG (2009–2020), and Global CMT (1976–2022) catalogs, together with records of damaging earthquakes and tsunamis. A total of 7,746 earthquakes were analyzed and integrated with a published seismic tomography model based on the AK135 velocity model through spatial mapping and vertical cross-sections constructed at 1° longitude intervals. The results show a continuous subduction system extending beneath southern Java from west to east. Shallow earthquakes (<100 km) are concentrated near megathrust interface, intermediate-depth events (100–300 km) delineate Wadati–Benioff zone, and deep earthquakes (>300 km) indicate continued slab descent into the upper mantle. Cross-sectional analysis reveals along-strike variations in slab geometry, with relatively shallow slab configurations in the western segment and steeper geometries toward the central segment. Tomographic images show high-velocity anomalies associated with the subducting slab and low-velocity anomalies interpreted as mantle wedge regions. Focal mechanism solutions are dominated by thrust faulting at shallow depths, whereas normal and strike-slip faulting become more common at intermediate depths. These observations provide additional constraints on the relationship between slab geometry, deformation processes, fault activity, and seismic hazards in West and Central Java.